Análise VAR dos índices bolsistas SP500, FTSE100, PSI20, HSI e IBOVESPA - Nogueira, David do Coito (2018)
Made available in DSpace on 2018-09-05T14:08:34Z (GMT). No. of bitstreams: 1 3840_7597.pdf: 681402 bytes, checksum: 5fac5a82c814a0d705eaca80d4af433c (MD5) Previous issue date: 2014-11-05